2016
DOI: 10.1371/journal.ppat.1005546
|View full text |Cite
|
Sign up to set email alerts
|

cGAS Senses Human Cytomegalovirus and Induces Type I Interferon Responses in Human Monocyte-Derived Cells

Abstract: Human cytomegalovirus (HCMV) infections of healthy individuals are mostly unnoticed and result in viral latency. However, HCMV can also cause devastating disease, e.g., upon reactivation in immunocompromised patients. Yet, little is known about human immune cell sensing of DNA-encoded HCMV. Recent studies indicated that during viral infection the cyclic GMP/AMP synthase (cGAS) senses cytosolic DNA and catalyzes formation of the cyclic di-nucleotide cGAMP, which triggers stimulator of interferon genes (STING) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
165
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(180 citation statements)
references
References 82 publications
12
165
1
2
Order By: Relevance
“…However, near-complete depletion of IFI16 mRNA levels in HUVECs not only failed to diminish HMCV-induced IRF3 activation but also, in fact, significantly enhanced it (Fig. 3F), which is consistent with recently reported results showing that IFI16-deficient THP-1 monocytes produce increased levels of IFN-␤ after infection with HCMV (35). Taken together, these results definitively show that HCMV infection of primary endothelial cells activates a cytosolic DNAsensing pathway involving a cGAS-STING-TBK1-IRF3 axis, leading to the transcription of innate antiviral genes, including IFN-I and IFN-I-inducible genes.…”
Section: Hcmv Triggers a Robust Ifn-i Response In Endothelial Cellssupporting
confidence: 92%
“…However, near-complete depletion of IFI16 mRNA levels in HUVECs not only failed to diminish HMCV-induced IRF3 activation but also, in fact, significantly enhanced it (Fig. 3F), which is consistent with recently reported results showing that IFI16-deficient THP-1 monocytes produce increased levels of IFN-␤ after infection with HCMV (35). Taken together, these results definitively show that HCMV infection of primary endothelial cells activates a cytosolic DNAsensing pathway involving a cGAS-STING-TBK1-IRF3 axis, leading to the transcription of innate antiviral genes, including IFN-I and IFN-I-inducible genes.…”
Section: Hcmv Triggers a Robust Ifn-i Response In Endothelial Cellssupporting
confidence: 92%
“…With this in mind, host signaling pathways necessary for HCMV-induced ISG15 accumulation and conjugation were examined. For HCMV, engaging the cytoplasmic dsDNA sensor cGAS is responsible for activating the critical adaptor protein STING and triggering antiviral responses (34,35). To determine if ISG15 accumulation was cGAS dependent, NHDFs transfected with control NS siRNA or cGAS-specific siRNAs were infected with HCMV, and ISG15 abundance was measured by immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that the cGAS/STING-mediated cytosolic DNA-sensing signal pathway is important for cellular innate responses and intrinsic resistance to DNA virus infection (11)(12)(13). However, so far little is known about the countermeasures by DNA viruses, including herpes simplex virus 1 (HSV-1), against the cGAS/STINGmediated DNA sensing signal pathway.…”
mentioning
confidence: 99%